Intravenously Administered Nonsteroidal Anti-Inflammatory Drugs in Clinical Practice: A Narrative Review - Axel Maurice-Szamburski; Cyril Quemeneur; Romain Rozier; Philippe Cuvillon; Claude Ecoffey (Pharmacy)
Intravenously administered nonsteroidal anti-inflammatory drugs (NSAIDs) constitute a crucial component of multimodal analgesia strategies in surgical settings. This narrative review aims to provide an up-to-date evaluation of the efficacy, safety, and clinical use of intravenous (IV) NSAIDs for perioperative pain management in adults and children. The NSAIDs and selective COX-2 inhibitors (coxibs) approved in Europe for the short-term symptomatic treatment of acute, moderate perioperative pain via IV infusion in adults and/or children have been influenced by US and global guidelines and practice: the drugs primarily reviewed here are ibuprofen, ketorolac, ketoprofen, naproxen, paracetamol, and acetylsalicylic acid. Furthermore, intravenous ibuprofen is authorized for the short-term symptomatic treatment of fever. In contrast to intravenous ketoprofen, intravenous ibuprofen is authorized for administration to children over 6 years of age or weighing more than 20 kg. Overall, IV ibuprofen had a more favorable profile with regard to peri- and postoperative opioid sparing and pain relief. Oral ibuprofen and IV ibuprofen have similar levels of efficacy, although IV ibuprofen has a shorter onset of action and is required in patients who are unable to take oral medications. The frequency of significant adverse events appears to be similar for ibuprofen and paracetamol. Systematic reviews and meta-analyses report that intravenous NSAIDs reduce postoperative opioid consumption by approximately 20–60%, improving pain management with fewer opioid-related side effects. In indications in infants, the choice of medication is limited, and the oral route is not always feasible; IV formulations of ibuprofen are preferred in this setting. Topics for further research should include head-to-head trials of IV NSAIDs.